Enhancement of soybean nodulation by seed treatment with non–thermal plasmas - Pérez Pizá, María Cecilia (2020)
Soybean (Glycine max (L.) Merrill) is one of the most important crops worldwide providing dietary protein and vegetable oil. Most of the nitrogen required by the crop is supplied through biological N2 fixation. Non-thermal plasma is a fast, economical, and environmental-friendly technology that can improve seed quality, plant growth, and crop yield. Soybean seeds were exposed to a dielectric barrier discharge plasma operating at atmospheric pressure air with superimposed flows of O2 or N2 as carrying gases. An arrangement of a thin phenolic sheet covered by polyester films was employed as an insulating barrier. We focused on the ability of plasma to improve soybean nodulation and biological nitrogen fixation. The total number of nodules and their weight were significantly higher in plants grown from treated seeds than in control. Plasma treatments incremented 1.6 fold the nitrogenase activity in nodules, while leghaemoglobin content was increased two times, indicating that nodules were fixing nitrogen more actively than control. Accordingly, the nitrogen content in nodules and the aerial part of plants increased by 64% and 23%, respectively. Our results were supported by biometrical parameters. The results suggested that different mechanisms are involved in soybean nodulation improvement. Therefore, the root contents of isoflavonoids, glutathione, auxin and cytokinin, and expansin (GmEXP1) gene expression were determined. We consider this emerging technology is a suitable pre-sowing seed treatment.